Analisis Pengaruh Disiplin, Kepribadian dan Pelatihan Terhadap Kompetensi (Studi Pada Peserta Pelatihan Di Balai Latihan Kerja Kota Bogor) - Isman, Raden Panji Mochamad Ageng; purnahayu, indu; Aminda, Renea Shinta (Jurnal Manajemen, 2020)
The problem that is used as the object of research is the knowledge competency of the trainees is very low. The attitude competency of the trainees is very low. The skills competency of the trainees is very low. This study aims to: 1) Know the effect of discipline on competence, 2) Know the influence of personality on competence, 3) Know the effect of training on competence, 4) Know the effect of discipline and personality together on competence, 5) Know the effect of discipline and training jointly on competence, 6) Knowing the influence of personality and training together on competence, and 7) Knowing the effect of discipline, personality, and training together on competence. The data collection technique was using a questionnaire given to the participants of the training as 125 respondents. The hypothesis used is simple regression analysis and multiple regression analysis. The results showed that: 1) There was a positive and significant effect of discipline on competence, 2) There was a positive and significant influence on personality on competence, 3) There was a positive and significant effect of training on competence, 4) There was a positive influence and significant discipline and personality together towards competence. 5) There is a positive and significant effect of discipline and joint training on competence, 6) There is a positive and significant influence on personality and training together on competence, and 7) There is a positive and significant influence on discipline, personality, and joint training of competencies.